The psychometric properties of a novel task-based dance self-efficacy measure for older adult dance program participants. Issue 1 (2nd January 2023) - Waugh, Martha; Grunseit, Anne C.; Mathieu, Erin; Merom, Dafna
ABSTRACT: Background: Self-efficacy for dance may reflect individual differences in factors likely to influence dance program participation. This study investigated the psychometric properties of six novel task-based dance self-efficacy (t-bDSE) questions for older adults participating in two large-scale dance intervention trials (N1  = 530; N2  = 131). Methodology: Internal consistency of t-bDSE was assessed and items validated according to age, gender, physical ability, cognitive status, psychosocial wellbeing, dance experience and exercise behaviour. Responsiveness of t-bDSE was investigated by comparing dance program participants to control groups. Results: Internal consistency was high (Cronbach's α = .88). Dance self-efficacy was weaker in participantswith less dance experience, poorer mental health, poorer cognitive and physical abilities, and insufficiently active. t-bDSE scores improved in aged-care trial participants (ηp 2  = .05, a moderate effect). Conclusions: The dance self-efficacy measure demonstrated good criterion and construct validity and can be included in future dance interventions to improve understanding of outcome variability and inform program evaluation.